Self-sustaining bio energy production community - Chan, Ramon Christopher M. (College of Architecture, University of the Philippines Diliman, 2014)
The world has limited resources. The current lifestyle of human beings with all the technological advancements requires at more than 2 earths to be sustained. With this fact, we tap into fossil fuels; energies of previous living things on the planet for energy, first with coal and then with oil. This phenomenon causes an imbalance between the staggering amounts of demand to the dwindling supply. Thus, scientists have been continuously searching for new energies that would sustain our civilization. One among many of these discoveries is Bio-Energy or energy from the Earth. This energy includes direct energy obtained from the Bio-Mass and stored energy from the Bio-Fuel. Bio-Mass is obtained from living or recently living organisms a stark contrast from fossil fuels. It is most often associated with plants or plant derived materials. Bio-Fuels is a stored form of this energy and is currently being used by countries of the European Union as well as the United State as an add mixture to most of their military fuel to reduce the dependency of gas prices with the turmoil in the Middle-East. Jatropha Curcas is a crop that can grow in depleted soil conditions. This plant requires low maintenance and less irrigation. This crop is only one of the many plants still on experiment. For direct bio-mass use, wood pellets from the dark of tress can be used to create combustion and thus energy produce energy. These sources of Bio energy though from plants will not endanger food security since they are either inedible or just waste products from flowering plants. This thesis is about creating a Bio Energy production facility with its own working community to promote green energy towards the country as well as to serve as a model for other facilities with the nature of helping the country’s energy demands.